2023
DOI: 10.3389/fmicb.2023.1268935
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationship between gut microbiota and bone mineral density: a Mendelian randomization study

Ying Wang,
Xuejian Zhang,
Guangjun Tang
et al.

Abstract: BackgroundThe gut microbiota has emerged as an intriguing and potentially influential factor in regulating bone health. However, the causal effect of the gut microbiota on bone mineral density (BMD) appears to differ throughout various life stages.MethodsWe conducted a Mendelian randomization (MR) analysis to investigate the potential causal relationship between gut microbiota and BMD in five distinct age groups: 0–15, 15–30, 30–45, 45–60, and 60 years and older. The analysis employed three different methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…39 An MR analysis demonstrated that Eubacterium ruminantium group was negatively correlated with bone mineral density. 40 Moreover, our study revealed that this GM taxon was a protective factor for SCLC. Eubacterium ruminantium group possessed the ability to produce short-chain fatty acids that inhibit proinflammatory cytokines such as IFN-γ, IL-1β, IL-6, IL-8, and TNF-α, as well as increase the expression of anti-inflammatory cytokines, such as IL-10 and TGF-β, resulting in an overall anti-inflammatory effect.…”
Section: Or (95% Ci)mentioning
confidence: 60%
“…39 An MR analysis demonstrated that Eubacterium ruminantium group was negatively correlated with bone mineral density. 40 Moreover, our study revealed that this GM taxon was a protective factor for SCLC. Eubacterium ruminantium group possessed the ability to produce short-chain fatty acids that inhibit proinflammatory cytokines such as IFN-γ, IL-1β, IL-6, IL-8, and TNF-α, as well as increase the expression of anti-inflammatory cytokines, such as IL-10 and TGF-β, resulting in an overall anti-inflammatory effect.…”
Section: Or (95% Ci)mentioning
confidence: 60%
“…This lower relative abundance of UCG-005 may be health-promoting given that UCG-005 is elevated in diabetes patients and is associated with elevated uric acid [72]. The genus Eubacterium_fissicatena_group was lower in prebiotic diet groups and is potentially harmful to bone mineral density [73] and correlates with obesity in a high-fat diet model [74]. Prebiotic diet also lowered Eubacterium_ruminantium_group, GCA-900066575, and Rikenellaceae_RC9_gut.…”
Section: Discussionmentioning
confidence: 96%
“…Alistipes is a gram-negative bacterium belonging to the phylum Bacteroidetes, and its main metabolites are succinic acid, acetic acid, and propionic acid ( Parker et al, 2020 ). An MR study on the causal relationship between the gut microbiota and bone mineral density (BMD) showed that Alistipes have a protective effect on BMD ( Wang et al, 2023 ). Furthermore, the relative abundance of Alistipes is decreased in osteoporosis patients ( Huang et al, 2022 ); however, we found that the expression abundance of Alistipes in OVX mice was significantly reduced, showing a strong positive correlation with gut barrier indicators, indicating that Alistipes may also be a potential mediator to regulate the microbiota-gut-bone axis.…”
Section: Discussionmentioning
confidence: 99%